Offshore Outsourcing of Customer Services and Consumer Behavior: Towards A Comprehensive Conceptual Framework - Sharma, Piyush; Mathur, R.; Dhawan, A. (2015)
Offshore outsourcing is a fast-growing aspect of the world economy today with companies striving to reduce cost and improve productivity by shifting parts of their operations to overseas service providers in order to remain competitive (McCartney 2003; Ross 2003). Existing research on offshore outsourcing is primarily focused into the labor and ethical issues of outsourcing or on the effects of strategic outsourcing decisions on organizations (Clott 2004; Razzaque and Sheng 1998). There is little research on the influence of outsourcing on consumers, their perceptions, attitudes and behaviors. However, organizations are already becoming more cautious about moving towards outsourcing because of concerns about dilution of their image, lower customer satisfaction, reduced brand loyalty and an increase in customer complaints due to real or perceived concerns about cultural differences, lower service standards and loss of privacy (Cornell 2004; Data-Monitor 2004; Economist 2001; Kennedy 2002; Reilly 1997; Roy 2003).